The hollow shell: children born of war and the realities of the armed conflict in Colombia - Sanchez Parra, Tatiana (International journal of transitional justice, 2018)
This article discusses tensions and dynamics around configuring children born as a result of wartime sexual violence as subjects within the realities in which transitional justice operates. Based on ethnographic research in Colombia, the article explores how a victimhood discourse and an explanatory framing to understand gender-based violence and sexual violence as a weapon of war, have restricted the emergence of these children as independent war-affected subjects. Instead, they have emerged as subjects that play a part in the social negotiations around victims of wartime sexual violence - for instance, gender and forced maternity - or around perpetrators and their constant presence in the history of the communities. To understand the plight and role of these subjects within the political community, transitional justice frameworks must contest the normative approach to harm, as these women and men were conceived by war but are not defined by it.